THE INTEGRATION OF MODERN SCIENCE IN THE INTERPRETATION OF THE VERSES OF THE COSMOS: A STUDY OF THE WORK OF ZAGHLUL AL-NAJJAR IN MUKHTARÂT MIN TAFSÎR AL-ÂYÂT AL-KAWNIYYAH FI AL-QUR'ÂN AL-KARÎM JUZ 1 - Maulidya Rahmani; Fadlan Nur Mubarok; Suhadi; Andi Rosa (Adisam Publisher, 2026)
This research aims to explore how modern science is integrated in the interpretation of the verses of the cosmos in the Qur'an through an analysis of the book Mukhtarât min Tafsîr al-Âyât al-Kawniyyah fi al-Qur'ân al-Karîm Juz 1 by Zaghlul al-Najjar. This study emerged in line with the development of the method of scientific interpretation in the study of the Qur'an today that seeks to connect the text of revelation with discoveries in modern science. The method used in this study is a literature review with a descriptive-analytical approach to the interpretation of the verses of the cosmos in the work. The data used came from the main sources, namely the books analyzed as well as various additional literature related to the interpretation of modern science and science. The findings of the study show that Zaghlul al-Najjar relates the verses of the cosmos to a variety of modern scientific concepts such as cosmology, geology, meteorology, and oceanography. This connection can be seen in the interpretation of verses that discuss the creation of the universe, the expansion of the cosmos, the structure of the earth and the role of mountains, the water cycle, and the phenomenon of the meeting of the two seas. With this approach, the content of the Qur'an is not only interpreted as a theological message, but also as a signal that can be investigated from a scientific point of view. The interpretation made reflects an attempt to show the harmony between the images in the Qur'an and modern scientific results. This research also reveals that Zaghlul al-Najjar's thought contributes significantly to the development of scientific interpretation by presenting an integrated model that involves revelation and science in an interdisciplinary manner. However, this approach requires methodological caution so as not to create an overly forced interpretation of scientific theories that are always changing. Therefore, this study emphasizes that scientific interpretation has great potential to enrich the study of the contemporary Qur'an and open up opportunities for dialogue between religion and science in understanding the universe.